Pengaruh Tekanan Waktu, Locus of Control, Tindakan Supervisi dan Materialitas terhadap Penghentian Prematur atas Prosedur Audit( Studi Empiris pada Kantor Akuntan Publik (KAP) di Surakarata dan Semarang) - Junaidi, Andi Tri, Dra.Rina Trisnawati, Ak. MSi.,Ph.D (2016)
This study aimed to analyze the effect of time pressure, locus of control, supervision measures, and materiality for premature sign off of the audit procedures. The population in this study is the auditors who work in public accounting firm in Surakarta and Semarang. The sample was selected by convenience sampling method and obtained the 57 auditor. Data retrieved by using the questionnaire. Before the data analysis, test the quality of data collection that are the validity and reliability that had been used. The method of analysis data is multiple linear regression. The results showed that the action of supervision, locus of control and materiality have significant effect on premature sign off of the audit procedures while time pressure has no effect on premature sign off of the audit procedures.